2018
DOI: 10.1159/000488822
|View full text |Cite
|
Sign up to set email alerts
|

CLIC1 Promotes the Progression of Gastric Cancer by Regulating the MAPK/AKT Pathways

Abstract: Background/Aims: Chloride intracellular channel 1 (CLIC1), which is a member of the chloride channel protein family, is associated with various human tumors. Recent studies have shown that CLIC1 is involved in the occurrence and development of gastric cancer (GC). However, the exact mechanism remains unclear in GC. Methods: Effects of CLIC1 on the progression of GC in vivo and in vitro and the potential underlying mechanisms have been investigated by analysing 54 patients with GC, as well as human gastric cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…CLIC1 has been reported to be upregulated in human malignant tumors of the colon, brain, liver, stomach, and lung. 14 , 22 , 24 , 26 , 27 It was evaluated to be the most penetrating receptor among commonly dysregulated proteins within three sarcomas. 23 This protein plays an important role in the metastasis of colonic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLIC1 has been reported to be upregulated in human malignant tumors of the colon, brain, liver, stomach, and lung. 14 , 22 , 24 , 26 , 27 It was evaluated to be the most penetrating receptor among commonly dysregulated proteins within three sarcomas. 23 This protein plays an important role in the metastasis of colonic cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 31 What is more, CLIC1 may be correlated with the regulation of integrin-family proteins, which leads to subsequent regulation of the PI3K–AKT, MAPK–p38, and MAPK–ERK pathways. 14 To evaluate the biological function of CLIC1 in OSCC pathogenesis further, we compared CLIC1 with tumor-associated genes using PCR. We found that CLIC1 was relevant to a variety of tumor genes, especially PA28B , MMP2, and MMP13, whereas PA28B and matrix metalloproteinases (MMPs) played an important role in tumor metastasis and invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The chloride intracellular channel 1 (CLIC1) is a member of the CLIC family. Additionally, it is also the most studied one in the family [17]. The effects of CLIC1 have been explored and reported in human cancers.…”
Section: Instructionmentioning
confidence: 99%
“…Integrins are a family of transmembrane receptors; they form heterodimeric complexes composed of α and β subunits. [10][11][12][13] The 18α and 8β subunits are members of approximately 24 different Integrin receptors, each of which is capable of binding to specific ligands. They function in specific signal transduction pathways and in cell-cell adhesion and the adhesion between cells and the ECM.…”
Section: Introductionmentioning
confidence: 99%